Assessment of Changes in Water Quality of Enim River, Muara Enim, South Sumatera, Indonesia to Determine Environmental Designations - Sinaga, Andi Parluhutan; Ibrahim, Eddy; Hadiah, Fitri (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
Enim river flows within several sub-districts in Muara Enim Regency, including Semendo Darat Laut, Semendo Darat Tengah, Semendo Darat Ulu, Tanjung Agung, Lawang Kidul, and Muara Enim. This study examines changes in the water quality of the Enim River due to domestic wastewater discharges and the presence of the coal mining industry and household industries. Water samples were taken from 4 sampling stations along the Enim River in 2018 and 2023. Data consisted of results of physical, chemical, and microbiological parameters. The status of river water quality was assessed from the pollution index. The results of Enim River surface water quality measurements showed that the parameters of total suspended solids, Dissolved Oxygen, iron (Fe), copper (Cu), oil, and grease concentrations had breached the criteria set for Class II water quality, referring to Government Regulation of the Republic of Indonesia Number 82 of 2001. The results showed that there has been a change in the water quality status of Enim River from 2018 to 2023. The river water pollution index was (1.43-2.47) in 2018 and (1.49-3.85) in 2023 (lightly polluted). Comprehensive water treatment and preventive measures are necessary to manage and mitigate additional pollution in the Enim River.